An Economics Analysis of Employability and Unemployment of Humanities and Social Sciences Graduates in Sri Lanka. (September 2022) - Dayaratna-Banda, O. G.; Dharmadasa, P. D. C. S.
The unemployment among arts, humanities and social sciences graduates has been a significant phenomenon in many countries in the world including Sri Lanka, which has received intense attention from policymakers in recent times in which the fault is often directed at the universities that produce these graduates. According to the Labor Force Survey of Sri Lanka, overall unemployment remained at 5.1% while the youth unemployment rate remained at 23.3% in 2019, which included more than 50, 000 unemployed graduates, most of whom were humanities and social sciences graduates. In this backdrop, this paper reviewed the causes of unemployment and the issues of the employability of humanities and social sciences graduates in Sri Lanka. The study revealed that the graduates in humanities and social sciences have not been employable mainly due to the fact that there has been a significant skills mismatch as graduates lack employable skills and attributes. Moreover, unemployment of humanities and social sciences graduates is caused by a number of factors including skills deficiency, occupational immobility, geographical immobility, technology change, a lack of sufficient jobs growth and various structural constraints in the economy. The study suggests that there is a need for significant structural reforms on both the supply side and the demand side to make graduates more employable and employed. While the government is required to play a leading role in these structural reforms to create more jobs for the graduates in humanities and social sciences, the higher education institutes need to undertake a major structural reform of study programmes through a vision that enables them to produce intellectually rich, and highly skilled graduates in humanities and social sciences.